IL-6 and TIMP-1 Correlated to Airway Pathogen Colonization and Predict Disease Severity in Patients with Non-Cystic Fibrosis Bronchiectasis - Lin HC; Hsieh MH; Lo YL; Huang HY; Huang SW; Huang CD; Chang PJ; Lo CY; Lin TY; Fang YF; Lin SM; Lin CY; et al. (Dove Medical Press, 2024)
Horng-Chyuan Lin,1- 3 Meng-heng Hsieh,1,2 Yu-Lun Lo,1,2 Hung-Yu Huang,1,2 Shih-Wei Huang,1,2 Chien-Da Huang,1,2 Po-Jui Chang,1,2 Chun-Yu Lo,1,2 Ting-Yu Lin,1,2 Yueh-Fu Fang,1,2 Shu-Min Lin,1,2 Chun-Yu Lin,1,2,* Ying-Huang Tsai1,2,4,* 1Department of Pulmonary and Critical Care Medicine, Chang Gung Memorial Hospital at Linkou, Taoyuan, Taiwan; 2College of Medicine, Chang Gung University, Taoyuan, Taiwan; 3Department of Respiratory Therapy, Chang Gung Memorial Hospital at Linkou, Taoyuan, Taiwan; 4Department of Pulmonary and Critical Care Medicine, Xiamen Chang Gung Hospital, Xiamen, 361028, People's Republic of China*These authors contributed equally to this workCorrespondence: Chun-Yu Lin, Department of Pulmonary and Critical Care Medicine, Chang Gung Memorial Hospital, 5 Fu-Hsing Street, Kweishan, Taoyuan, 33305, Taiwan, Tel +886-3-3281200 ext. 8467, Fax +886-3-3282474, Email pitiful1984@gmail.com Ying-Huang Tsai, Department of Pulmonary and Critical Care Medicine, Linkou Chang Gung Memorial Hospital, Chang Gung Medical Foundation and Department of Respiratory Therapy, College of Medicine, Chang Gung University, 5 Fu-Hsing Street, Kweishan, Taoyuan, 33305, Taiwan, Tel +886-3-3281200 ext. 8470, Fax +886-3-3282474, Email chestmed@cgmh.org.twBackground: Non-cystic fibrosis bronchiectasis is associated with airway pathogen colonization. We planned to investigate the inflammatory markers in patients with different airway pathogens and their correlation with disease severity.Methods: We enrolled patients aged between 20 and 75 from October 2021 to August 2022. All patients had sputum evaluation for bacterial and fungal cultures before enrollment, and were classified into four groups according to the culture results.Results: Forty-four patients with non-CF bronchiectasis and six controls were enrolled and categorized as follows: Group 1, no pathogens identified in sputum cultures (n = 14); Group 2, positive fungal culture results (n = 18); Group 3, positive P. aeruginosa culture results (n = 7); and Group 4, positive culture results for both fungi and P. aeruginosa (n = 5). Group 4 had significantly higher serum defensin α 1, IL-6 and tissue inhibitors of MMP (TIMP)-1 levels than group 1 patients. The serum levels of IL-6 and TIMP-1 were positively correlated with the FACED score and negatively correlated with distance-saturation product.Conclusion: Significantly higher levels of serum IL-6 and TIMP-1 were found in the patients who had concomitant fungal and P. aeruginosa colonization, and were closely related to clinical severity and may have important roles in disease monitoring.Keywords: TIMP-1, non-cystic fibrosis bronchiectasis, clinical severity